2018
DOI: 10.2174/1874325001812010364
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Tilt Angle Differences Between Symptom-Free Young Subjects and Elderly Patients Scheduled for THA: The Rationale for Tilt-Adjusted Acetabular Cup Implantation

Abstract: Background:The question whether Pelvic Tilt (PT) angles measured in the supine position are adequate for the alignment of the acetabular cup without an adjustment for anatomical differences between patients is of clinical importance. The aim of this work was to test for factors that can significantly affect PT angles.Methods:In the present retrospective cohort comparison, the PT angles of 12 Symptom-Free Young Subjects (SFYS) and 45 patients scheduled for Total Hip Arthroplasty (THA) were compared. The data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Specifically, acetabular version has been shown to increase with decreasing pelvic tilt angle. 8 , 19 , 27 , 39 Babisch et al 3 found that acetabular version changed by 4° for every 5° of pelvic tilt angle, and Stem et al 42 found that the greatest effect on acetabular version was when pelvic tilt angle was greater than 6°. Pelvic tilt is important in range of motion: increasing pelvic tilt decreases the impingement-free range of motion of the hip.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, acetabular version has been shown to increase with decreasing pelvic tilt angle. 8 , 19 , 27 , 39 Babisch et al 3 found that acetabular version changed by 4° for every 5° of pelvic tilt angle, and Stem et al 42 found that the greatest effect on acetabular version was when pelvic tilt angle was greater than 6°. Pelvic tilt is important in range of motion: increasing pelvic tilt decreases the impingement-free range of motion of the hip.…”
Section: Discussionmentioning
confidence: 99%
“… 34 , 43 When transitioning from supine to standing, there is an increase in pelvic tilt angle. 27 , 34 , 44 However, the supine position is a common, standardized, position in obtaining radiographs to assess the young adult hip. 7 What was more important for this anatomic study was to determine the interaction of the acetabular and spinopelvic morphology, and CT imaging in the supine position provided the necessary information.…”
Section: Discussionmentioning
confidence: 99%
“…The absolute angular value of the functional change in the pelvic tilt, i.e. the difference in angular value between the standing and supine positions, is equal to the absolute value of the PT change in APP [15]. It is essential to identify cases where a change of pelvic position occurs with a change of body position, as a serious tilt change can signi cantly affect the possible results of surgical procedures involving implantation of a hip joint, particularly with regard to the Lewinnek Safe Zone [4,10].…”
Section: Discussionmentioning
confidence: 99%
“…The search for a safe assessment of at least one of the parameters of pelvic tilt led to the ongoing development of an ultrasound-based navigation method using the Smart Navigated Ultrasound (SNU) navigation system by B. Braun Aesculap [15,16]. The system measures the PT in the APP.…”
Section: Eftekhary Et Al Report That In Cases Of Different Functional...mentioning
confidence: 99%